ANALYSIS OF MODELS AND METHODS FOR ASSESSING THE STRENGTH CHARACTERISTICS OF POLYMER COMPOSITE MATERIALS - Mikosianchyk, Oksana; Pedan, Yevhen; Mnatsakanov , Rudolf; Khimko, Andrii; Bogdan, Svitlana; Chava, Kateryna (Problems of Friction and Wear, 2023)
The expediency of combining complex design systems and conducting standardized mechanical tests in the development of new composite materials in order to increase the reliability of products and structures is substantiated. The analysis of modern software complexes of finite element analysis SolidWorks, ANSYS, Abaqus and Patran/Nastran for modeling the properties of composite materials was carried out. The peculiarities of predicting various forms of destruction of polymer composite materials are determined, estimates of potential mechanisms of destruction, PCM damage models depending on the software complex used in the design of products from composite materials are given. The application of the edge effects model in layered composites, displacement compatibility models, adhesion models, linearized three-dimensional fracture criteria and other fracture models with the rate of energy release, the method of virtual crack closure in calculating the damage resistance of laminated composite structures at the design stages is considered. The main aspects of methods of research and determination of mechanical properties of composite materials under tension and compression according to ISO and ASTM standards are considered. The procedure for creating a regulatory and technical base in the field of production and application of PCM is analyzed from the standpoint of bringing the national standardization system closer to international and European norms and rules.